2016
DOI: 10.1002/eqe.2730
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of performance of non‐invasive upgrade strategy for beam–column sub‐assemblages of poorly designed structures under seismic type loading

Abstract: Summary Beam–column sub‐assemblages are the one of the most vulnerable structural elements to the seismic loading and may lead to devastating consequences. In order to improve the performance of the poorly/under‐designed building structures to the critical loading scenarios, introduction of steel bracing at the RC beam–column joint is found to be one of the modern and implementable techniques. In the present work, a diagonal metallic single haunch/bracing system is introduced at the beam–column joints to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Moreover, structural interventions need to have enhanced characteristics such as being rapid, minimally invasive, cost-effective and subsequently financially viable, in order to qualify as adequately resilient solutions. Some examples with various novel materials and techniques can be found in [4][5][6][7][8][9], and a state-of-the-art report and guidance in [10]. The research reported below seeks to address this issue with a focus on the use of advanced superelastic shape memory alloys for use at the critical joint locations of framed concrete structures.…”
Section: Introduction 1motivation Fundamental Principles and Backgrou...mentioning
confidence: 99%
“…Moreover, structural interventions need to have enhanced characteristics such as being rapid, minimally invasive, cost-effective and subsequently financially viable, in order to qualify as adequately resilient solutions. Some examples with various novel materials and techniques can be found in [4][5][6][7][8][9], and a state-of-the-art report and guidance in [10]. The research reported below seeks to address this issue with a focus on the use of advanced superelastic shape memory alloys for use at the critical joint locations of framed concrete structures.…”
Section: Introduction 1motivation Fundamental Principles and Backgrou...mentioning
confidence: 99%
“…Qu et al proposed an unconstrained gusset connection for the buckling restrained braces in RC frames to mitigate the complicated and harmful interactions between the gusset plate and the adjoining columns. Sasmal and Nath proposed a diagonal metallic single haunch/bracing system for protecting the beam‐column joints of poorly designed structures under seismic cyclic loading. In addition to these research efforts, other researchers have investigated the effects of different types of structural detailing on the progressive collapse resistance of RC beams.…”
Section: Introductionmentioning
confidence: 99%